Endothelin‐1 enhances the proliferation of normal human melanocytes in a paradoxical manner from the TNF‐α‐inhibited condition, but tacrolimus promotes exclusively the cellular migration without proliferation: a proposed action mechanism for combination therapy of phototherapy and topical tacrolimus in vitiligo treatment. (9th March 2012) - Lee, K.Y.; Jeon, S.Y.; Hong, J.W.; Choi, K.W.; Lee, C.Y.; Choi, S.J.; Kim, J.H.; Song, K.H.; Kim, K.H.
Abstract: Background  Vitiligo is an acquired pigmentary disorder caused by the destruction of melanocytes. Two of the major theories regarding the pathogenesis of vitiligo are the autoimmune theory and autocytotoxicity theory, but, the precise pathogenetic mechanism is still not clarified. Objectives  We investigated the effects of ET‐1, tacrolimus and tumour necrosis factor‐α (TNF‐α) on proliferation and migration of cultured normal human melanocytes (NHMs). We also sought to clarify the theoretical rationale underlying the topical tacrolimus monotherapy or tacrolimus‐UV combination therapy as tools for vitiligo treatment. Methods  The effects of ET‐1, tacrolimus and TNF‐α on proliferation/migration of cultured NHMs were investigated by MTT assay/Boyden chamber transwell migration assay. We also examined roles of CXC‐chemokine receptor II (CXCR II) and matrix metalloproteinases (MMPs) in such conditions. Results  ET‐1 exerted a stimulatory effect on melanocyte proliferation and migration, but, tacrolimus exerted a stimulatory effect only on melanocyte migration higher than ET‐1. TNF‐α inhibited melanocyte proliferation in a dose‐dependent manner. Paradoxically, TNF‐α‐pretreated NHMs exhibited an enhanced proliferative efficiency after being switched to ET‐1. We found CXCRII was highly expressed in TNF‐α‐incubated melanocytes than the agents‐free control, and ET‐1 treatment after TNF‐α preincubation showed the higher levels of CXCRII expression than the condition incubated with TNF‐α alone. Moreover, the greater activities of MMP‐2 and MMP‐9 induced by tacrolimus than ET‐1, reflected tacrolimus would enhance migration stimulatory effect in cultured NHMs. Conclusions  Topical tacrolimus can be used an effective agent for vitiligo treatment as monotherapy, maybe due to its migration stimulatory action or TNF‐α inhibitory property, and also as a component in combination therapy with UV treatment, considering the more upregulated MMPs activities are induced and the more effective migrations are feasible by itself than ET‐1.